Recover value metals from spent lithium-ion batteries via a combination of in-situ reduction pretreatment and facile acid leaching. (15th April 2023) - Zhang, Yu; Yu, Meng; Guo, Jiangmin; Liu, Shaojun; Song, Hao; Wu, Weihong; Zheng, Chenghang; Gao, Xiang
Graphical abstract: Abstract: The pretreatment of cathode material before leaching is crucial in the spent lithium-ion battery hydro-metallurgical recycling. Here research demonstrates that in-situ reduction pretreatment could dramatically improve the leaching efficiencies for valuable metals from cathodes. Specifically, calcination under 600 °C without oxygen using alkali treated cathode can induce in-situ reduction and collapse of oxygen framework, which is ascribed to the carbon inherently contained in the sample and promote the following efficient leaching without external reductants. The leaching efficiencies of Li, Mn, Co and Ni can remarkably reach 100%, 98.13%, 97.27% and 97.37% respectively. Characterization methods, such as XRD, XPS and SEM-EDS, were employed and revealed that during in-situ reduction, high valence metals such as Ni 3+, Co 3+, Mn 4+ can be effectively reduced to lower valence states, conducive to subsequent leaching reactions. Moreover, leaching processes of Ni, Co and Mn fit well with the film diffusion control model, and the reaction barrier is in accordance with the order of Ni, Co and Mn. In comparison, it is observed that Li was leached with higher efficiency regardless of the various pretreatments. Lastly, an integral recovery process has been proposed and economic assessment demonstrates that in-situ reduction pretreatment increases the benefit with a negligible cost increase.